Factors contributing to the declining enrolment of BBA (HONS) marketing (PLK) program with specific reference to UiTM Samarahan Campus/ Albert Jingga Aneng - Aneng, Albert Jingga (2004)
The ultimate aim of gathering and compiling data in these studies is to identify the factors that contribute to the declining enrolment of BBA (Hons) Marketing, PLK program. Thus, this study intends to gauge the prospect's awareness, preference level, attitude and perception towards UiTM BBA (Hons) Marketing, PLK program. Furthermore it is hoped that the followings findings would enable the UiTM Samarahan Campus to formulate new marketing strategies and plan of actions to stimulate more awareness among prospects i.e. the Adult Working Bumiputera.